Effect of Light-Emitting Diodes and Ultraviolet Irradiation on the Soluble Sugar, Organic Acid, and Carotenoid Content of Postharvest Sweet Oranges (Citrus sinensis (L.) Osbeck) - Linping Hu; Can Yang; Lina Zhang; Jing Feng; Wanpeng Xi (Molecules, 2019)
Mature ‘Hamlin’ sweet oranges (Citrus sinensis (L.) Osbeck) were irradiated using light-emitting diodes (LEDs) and ultraviolet (UV) light for six days after harvest. Based on evaluation of the basic ripening parameters of fruits, the contents of soluble sugars, organic acids, and carotenoids were analyzed (in pulps) on the sixth day by high-performance liquid chromatography (HPLC). The results showed that LED and UV irradiation not only accelerated orange ripening but also caused significant changes in the soluble sugar, organic acid, and carotenoid content. Compared with fruit subjected to dark shade (DS) treatment, the total soluble sugar, fructose, and glucose contents increased significantly in UV-treated (UVA, UVB, and UVC) fruits, while the sucrose content increased remarkably in white light, UVB, and UVC-treated fruits (p < 0.05). UV treatment was associated with inducing the largest effect on the total soluble sugar content. Except for UVB, other types of light notably induced an accumulation of the total organic acid content, none but blue light and red light markedly induced citric acid accumulation (p < 0.05). Interestingly, only the red light and dark shade treatments had markedly positive effects in terms of inducing carotenoid accumulation, including the total carotenoid, isolutein, zeaxanthin, lutein, neoxanthin, all-trans-violaxanthin, phytofluene, cis-ζ-carotene, and β-carotene concentrations. Other light treatments had significantly negative effects on carotenoid accumulation (p < 0.05). Therefore, soluble sugar, organic acid, and carotenoid accumulation in sweet oranges vary depending on the levels of UV and LED irradiation. Appropriate light irradiation is a potentially effective way to maintain or improve postharvest fruit quality.